2013
DOI: 10.1186/2193-1801-2-382
|View full text |Cite
|
Sign up to set email alerts
|

Novel xylanases from Simplicillium obclavatum MTCC 9604: comparative analysis of production, purification and characterization of enzyme from submerged and solid state fermentation

Abstract: The production of extracellular xylanase by a newly isolated fungus Simplicillium obclavatum MTCC 9604 was studied in solid-state and submerged fermentation. Multiple xylanases and endoglucanases were produced by the strain during growth on wheat bran in solid state fermentation (SSF). A single xylanase isoform was found to be produced by the same fungus under submerged fermentation (SF) using wheat bran as sole carbon source. Enzyme activity, stability and the protein yield were much higher in SSF than SF. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 29 publications
(32 reference statements)
2
18
0
Order By: Relevance
“…Xylanase was strongly inhibited in the presence of Cu 2+ and Hg 2+ . Similar results were observed in case of Bacillus subtilis [34], Bacillus halodurans PPKS-2 [35], and Simplicillium obclavatum [36]. It has been reported that the xylanase activity was inhibited by Hg 2+ ion, which might be due to its interaction with sulfhydryl groups of cysteine residue in or close to the active site of the enzyme [37].…”
Section: Effect Of Metal Ions On Enzyme Activity and Stabilitysupporting
confidence: 84%
“…Xylanase was strongly inhibited in the presence of Cu 2+ and Hg 2+ . Similar results were observed in case of Bacillus subtilis [34], Bacillus halodurans PPKS-2 [35], and Simplicillium obclavatum [36]. It has been reported that the xylanase activity was inhibited by Hg 2+ ion, which might be due to its interaction with sulfhydryl groups of cysteine residue in or close to the active site of the enzyme [37].…”
Section: Effect Of Metal Ions On Enzyme Activity and Stabilitysupporting
confidence: 84%
“…Zymography is used for the detection of enzymatically active protein bands in polyacrylamide gels. It is one of the most effective methodology for studying hydrolytic isozymes …”
Section: Resultsmentioning
confidence: 99%
“…BCC7928 showed a well‐defined activity band on a gel containing 0.2% wt/vol, Birchwood xylan . Roy et al used Birchwood xylan (2% wt/vol) for zymographic analysis, whereas Cano‐Ramírez et al and Sinma et al reported zymographic analysis of xylanase enzyme using Beachwood xylan substrate (1% wt/vol). Kumar et al supplemented gel with Birchwood xylan for zymographic analysis of xylanase enzyme.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies involving the production of fungal xylanases in solid-state fermentation have shown to obtain very high yields of xylanases as compared with that in the submerged fermentation method. This could be as a result of a poor oxygen supply and shear disruption of fragile fungal biomass in the stirred-tank reactor used for submerged fermentation (Roy et al, 2013;Jain et al, 2013;Gasper et al, 1997).…”
Section: Solid-state Fermentationmentioning
confidence: 99%